Taxonomy and Incorporation of Violence in the Contemporary Peruvian Police Novel - Delgado Del Aguila, Jesús Miguel (Cuadernos de Literatura, 2020)
This paper periodizes and develops the concomitant paradigms of the police novel, to extrapolate them in an incipient Peruvian context with texts that meet the essential requirements to be called that way. Violence is an inexorable element for receptive efficacy and its creative treatment, as well as knowledge of related topics, such as Law, Politics, Sociology, Police Forces, etc. For this, it will be corroborated with the definition of this genre (as Tzvetan Todorov mainly bases it) and the hegemonic taxonomy of its subgenres: enigma novel, problem novel, black novel, whodunit, historical police novel, police novel of historical period and novel criminal.